Developing CLE in Myanmar-Lessons Learned and Global Guidance - Bruce A Lasky (The Indonesian Journal of International Clinical Legal Education, 2019)
This paper, Developing CLE in Myanmar: Lessons Learned and Global Guidance, is an adaptation of an advocacy paper entitled The Global Path and Future of CLE in Myanmar. It draws from findings generated over more than three years of BABSEACLE’s work, often conducted in collaboration with New Perimeter (DLA Piper’s global pro bono affiliate) and Herbert Smith Freehills (HSF), hereafter referred to collectively as the “Consortium.” The Consortium partnered with eighteen university law departments across Myanmar to implement Clinical Legal Education (CLE) programs in cooperation with a wide range of local stakeholders (2013–present). The paper outlines key strategies that, in the author’s view, are essential for ensuring the sustainable development of a nationwide CLE program in Myanmar, while also presenting insights and lessons learned that hold relevance both regionally and globally. This initiative was supported extensively by the United Nations Development Programme (UNDP), the United States Agency for International Development Promoting Rule-of-Law Project (USAID PRLP), and other related organizations. The paper highlights how the application of regional and global experiences has enabled CLE in Myanmar to progress from its early beginnings into a growing and dynamic movement advancing legal education reform and access to justice. This movement has generated notable impacts within both educational and legal sectors. The paper evaluates the effects of implementing a nationwide CLE program in Myanmar from early 2013 to the present, and simultaneously serves as a timely resource for planning, developing, implementing, or strengthening CLE programs in Myanmar and beyond. It also provides practical recommendations aimed at facilitating the expansion, institutionalization, and long-term sustainability of CLE in Myanmar and in other jurisdictions.